ASSESSMENT OF ENVIRONMENTAL RISKS OF GENETICALLY MODIFIED PLANTS - Nodari, Rubens Onofre; Guerra, Miguel Pedro (Science & Technology Journals, 2001)
The precision and the power of genetic manipulation in vivo increased in the last decades as a function of the advancement of the molecular studies. One of the questions not resolved as yet is related with the environmental impacts and risks posed by large-scale cultivation of GMO. The hazards to the biodiversity after legal approval and release are provided by the transgene properties in the ecosystem or its transference and expression in other species. The addition of a new genotype in a plant community can cause several undesirable effects, such as the displacement or elimination of a non domesticated species, species exposure to a new pathogens or toxic agents, generation of super weeds or pests, genetic pollution, genetic erosion, and interruption of the nutrient and energy recycling. Thus, before the release for the large scale cropping of a plant transgenic variety it should be done an environmental impact study, which must includes the risk assessment, step by step and case by case. The scope of the risk assessment should be based on a matrix, being one axis the spatial scale (plant, plot, farm, region) and the other axis the direct and indirect effects on agriculture, ecology, and socio-economy.